The scientific impact of applied biomechanics research in artistic gymnastics - Potop, V.; Manolachi, V. (Revista Romaneasca pentru Educatie Multidimensionala, 2020)
The paper investigates the scientific impact of applied biomechanics research in artistic gymnastics. Therefore, biomechanics studies conducted from 2012 to 2014 and published so far were analysed. The learning macro-methods (M-ML) of gymnasts in basic specialization training stage (EPSB) were scientifically argued and practically applied. The biomechanics structure used video-computerized method and postural landmarks method, which identified, measured and analysed the technique key elements in vaults, uneven bars, balance beam and floor. The study results highlighted improved kinematic and dynamic parameters of the key elements of the analysed exercises technique by efficient use of M-ML in training.The analysis of the specialized literature compared with the performed studies reveals the research interest, citations, recommendations and reads. The scientific acknowledgment of publications in ResearchGate academic profile proves the efficiency of methodology application in preparation, which can serve as training method in gymnastics branches and related sports fields as well.